2008
DOI: 10.3141/2047-08
|View full text |Cite
|
Sign up to set email alerts
|

Simple Approach to Estimating Changes in Toll Plaza Delays

Abstract: Toll plazas are important components of the road infrastructure, especially on urban highways. They can have adverse capacity and safety impacts on traffic. However, the plazas serve an important purpose, namely, revenue generation for highway agencies. Various traffic management and electronic toll collection strategies, including regular and high-speed E-ZPass and time-of-day pricing, are also implemented as part of toll plaza operations to change traffic supply and demand characteristics and improve network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Level of Toll Plaza. Abdul Majid et al [12], Mahdi et al [13,14], and Ozmen-Ertekin et al [15] used the Markov chain system to study the factors that cause congestion and service level decline in Toll Plaza and found that the main factors include waiting queue length, delay time, and heavy vehicles. Jack and Haitham [16] used analytic hierarchy process to evaluate the service level of eight different toll plazas.…”
Section: Research On Servicementioning
confidence: 99%
“…Level of Toll Plaza. Abdul Majid et al [12], Mahdi et al [13,14], and Ozmen-Ertekin et al [15] used the Markov chain system to study the factors that cause congestion and service level decline in Toll Plaza and found that the main factors include waiting queue length, delay time, and heavy vehicles. Jack and Haitham [16] used analytic hierarchy process to evaluate the service level of eight different toll plazas.…”
Section: Research On Servicementioning
confidence: 99%
“…They have been used to simulate traffic operations at POEs and toll plazas. Most studies reported in public sources modeled toll plazas [see for example, Ozbay et al (5), Nezamuddin and Al-Deek (6), and Ozman-Ertekin et al (7)], with the exception of Quadstone (4), which was for a POE.…”
Section: Literature Review Microscopic Traffic Simulation Toolsmentioning
confidence: 99%